Análise espacial de populações naturais de Dipteryx alata Vogel.: Subsídio para coleta de sementes - Lima, Diana Carla de Oliveira Santana [UNESP] (2016)
The spatial distribution pattern of tree species is one of the most important factors for the understanding of the ecological interrelationships occurring in a population or community forestry, it is vital to the understanding of how a certain species uses the resources available to establish and reproduce in a given space. Interpretation of the results of the spatial analysis of tree species provides significant subsidies for the understanding of these phenomena and indication of individuals for genetic conservation programs and forest promotion. In this context, the objective of the work was to study the spatial distribution of six natural populations of arborea specie baru (Dipteryx alata Vogel.) using the Moran index associated with a Geographic Information System and descriptive statistics of their silvicultural attributes. These populations are located in the municipalities of Paulo de Faria/SP, Campina Verde/MG, Ituiutaba/MG, Brasilândia/MS, Campo Grande/MS e Itarumã/GO. All populations had a growth over 45 cm in relation to the DAP (Diameter at Breast Height) attribute. Taking into account that the DAP attribute has a higher dendrochronological correlation, the estimated age of these natural populations would be in the range between 40 and 63 years. As regards the calculation of Moran index, populations of Ituiutaba and Itarumã presented random spatial distribution pattern, pointing high variability among its individuals, so the collection of seeds for ex situ conservation of this species in these samples would be preferably indicated. Regarding the analyzed soils, mostly, the spatial distribution of attributes indicated a high acidity and a low concentration of organic matter content. The presence of mother trees in different classes of organic matter and pH, is an indication that the populations studied have adaptability in different soil conditions.